2021
DOI: 10.1371/journal.pone.0258387
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effects of nurses ‘personal and organizational values between organizational commitment and turnover: Cross-sectional study

Abstract: Background The values of individuals and organizations are the core factors driving and guiding nurses’ decision-making and actions. Previous studies mainly focused on the impact of organizational commitment and other influencing factors on turnover intention. Aim To explore the mediating effect of personal and organizational values matching the relationship between organizational commitment and turnover intention of nursing staff. Methods A cross-sectional survey of 490 subjects in four tertiary hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…This research found a significant negative relationship between turnover intention and organizational commitment, so it is important to increase organizational commitment as a strategy to retain the best nurses and keep them committed to organizational goals (Callado et al, 2023). In line with research by Wei et al (2021), the results of research on 490 nurses in four hospitals in Tianjin, indicated that there was a negative correlation between organizational commitment and turnover intention (Wei et al, 2021). In addition, the results of research by Wu et al (2022) show that organizational commitment is negatively related to the turnover intention of health service workers (Wu et al, 2022).…”
Section: H3: Job Burnout Has a Positive Effect On Turnover Intentionsupporting
confidence: 80%
See 1 more Smart Citation
“…This research found a significant negative relationship between turnover intention and organizational commitment, so it is important to increase organizational commitment as a strategy to retain the best nurses and keep them committed to organizational goals (Callado et al, 2023). In line with research by Wei et al (2021), the results of research on 490 nurses in four hospitals in Tianjin, indicated that there was a negative correlation between organizational commitment and turnover intention (Wei et al, 2021). In addition, the results of research by Wu et al (2022) show that organizational commitment is negatively related to the turnover intention of health service workers (Wu et al, 2022).…”
Section: H3: Job Burnout Has a Positive Effect On Turnover Intentionsupporting
confidence: 80%
“…These results are consistent with earlier research. (Callado et al, 2023;Wei et al, 2021;Wu et al, 2022) making it important to increase organizational commitment as a strategy to retain the best nurses and keep them committed to organizational goals (Callado et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these doctors are younger, have intermediate or junior titles, and are in their own rapid growth period, so they expect hospitals to provide more on-the-job training and career development opportunities. According to research by Khullar (2018), Chen (2015), and Wei (2021) [ 32 34 ], the main reason why young and middle-aged doctors can accept huge work pressure and medium-low pay is that tertiary hospitals can provide the resources needed to improve their ability. Therefore, the hospital management should pay attention to the material and spiritual incentive strategy in the development responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, they provide a variety of forms of training opportunities for helping one improve self ability and realize self-value, increasing its sense of belonging to the hospital. To some extent, it also can avoid poor hospital development responsibility and hospital youth talent drain [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant variable may be the organizational climate or culture. Authors such as Wei et al (2021) have already shown how this variable adds valuable information to understand the impact of different perceptions of the organizational environment of public employees.…”
Section: Limitations and Future Researchmentioning
confidence: 99%